P03.06.B Proton irradiation (PT) for benign meningiomas, Grade I clinical experience of the first 100 patients from REGI-MA-002015. (5th September 2022) - Lütgendorf-Caucig, C; Hug, E; Pelak, M; Flechl, B; Mock, U; Fossati, P; Mumot, M; Carlino, A; Georg, P; Georg, P
Abstract: Background: Meningiomas are the most common CNS tumors and the majority is regarded as benign. However, a subset of patients presents with complex tumors involving several anatomic compartments of the skull base - eluding any concepts of gross total resection. Proton therapy (PT) is applied as definitive treatment for primary or recurrent disease or postoperatively following subtotal resection. We report on the first 100 adult patients treated with PT at MedAustron. Material and Methods: All patients were enrolled in a prospective registry trial (ClinicalTrials.gov Identifier: NCT03049072). Target volume definition was based on CT, MR and DOTA-PET/CT. PT treatment plans were generated by applying a Simultaneous Integrated Boost (SIB) concept with the Single Field-optimisation method and utilizing 2-4 beams per plan with a beam spacing of >30°. Prescribed doses to PTV1 were 50.49Gy_RBE at 1.87Gy_RBE/fr and 54.0Gy_RBE at 2.0Gy_RBE/fr to PTV2 in overall 27 fractions. Follow up status was assessed by MRI at 6, 12 months and annually thereafter, side effects were assessed using CTCAE v4.0. and quality of life (QoL) using EORTC-CTC30 and BN20 questionnaires. The scores entered by the patients were added and normalized to 0-100 scale according to previously described protocols. Results: Between 08/2017 and 04/2021, 100 patients were treated, 22% (n=22) male and 78% (n=78) female patients. Median age at therapy was 54a (25a-82a). In 57% (n=57) PT was the definitive treatment (no resection or surgery >12 mo prior to PT). 43% (n=43) underwent postoperative PT with at least one surgery (range 1-3), and median time from last resection to start of PT of 6mo (3mo-11mo). 89% (n=89) meningiomas were located in the skull base with involvement of multiple anatomic compartments. The median GTV size was 24cc (1cc-226cc) and the median CTV 41cc (2cc-352cc), respectively. At median follow-up of 31.1 months (range 6.6-51.6), 2 local in-field failures were observed (both patients treated postoperatively) resulting in disease-specific survival of 100% and local control of 98% at 3 years, respectively. No > Grade 2 acute toxicity was observed. During follow-up two Grade 3 toxicities occurred: One patient developed symptomatic radiation induced brain lesion (RIBL) which resolved within 12 month; one patient was hospitalized for new onset of epilepsy without corresponding radiographic findings. 9% (n=9) developed G1/G2 RIBL, which resolved spontaneously. The general QoL including the global health status and all functioning domains remained stable and did not decrease significantly following PT. Conclusion: First clinical data demonstrate that PT based on a SIB concept is a safe and efficient treatment of anatomically complex, low grade meningiomas. Acute and late toxicity incidences in our series were low with excellent, prospectively assessed preservation of QoL.